Presence of absence - Lim, Shu Xian (Nanyang Technological University, 2020)
Presence of Absence is a collection of images and videos that seeks to explore the fragmentary nature of memory. This project begins with the attempt to reconcile the feeling of not being at home, even though I am physically in one. Through re-accessing past memories and photographing objects that look familiar, I hope to confront the fear of time and loss as I preserve my imaginative record of childhood. By combining three different components - photographic prints, photomontage videos and switchable smart film in my final presentation, it communicates the impulse to 'rescue' the past from erasure, at the same time it also reflects nostalgia as a deception of memory.